Polymeric membrane electrode-based biosensor for detection of methadone: Enhancing doping control in athletes - Guangyu Han; Wenjuan Zhang (Alexandria Engineering Journal)
This work aimed to develop a simple, very stable, and sensitive biosensor to detect methadone for athlete doping monitoring by integrating polyaniline and graphitic carbon nitride on a glassy carbon electrode (PANI/g-C3N4/GCE). Using modified g-C3N4/GCE, the deposition approach was used to electrooxidize and polymerize aniline. The electrodeposited and polymerized aniline particles on g-C3N4 surfaces were confirmed by the structural analysis results. The addition of g-C3N4 to PANI produced a network film that improved stability and sensitivity and significantly increased electron mobility, according to cyclic-voltammetry and differential-pulse-voltammetry measurements. The DPV responses of PANI/g-C3N4/GCE indicated that this methadone sensor has sensitivity of 0.0891 μA/μM, linear-range of 1–520 μM, and detection limit of 4 nM. In this study, the proposed sensor's methadone detection capabilities were tested using prepared urine samples from four young athletes, ages 26–32. The sensor's accuracy and dependability are demonstrated by the significant recovery values (more than 97.00 %), suitable precision (RSD less than 4.69 %), and agreement between measurements made using the DPV and the methadone test kit. These findings demonstrate the developed sensor's potential to improve athletes' doping control by offering a dependable methadone detection technique.